2021
DOI: 10.3390/pharmaceutics13122031
|View full text |Cite
|
Sign up to set email alerts
|

MSC Secretome as a Promising Tool for Neuroprotection and Neuroregeneration in a Model of Intracerebral Hemorrhage

Abstract: Multipotent mesenchymal stromal cells (MSCs) are considered to be critical contributors to injured tissue repair and regeneration, and MSC-based therapeutic approaches have been applied to many peripheral and central neurologic disorders. It has been demonstrated that the beneficial effects of MSC are mainly mediated by the components of their secretome. In the current study, we have explored the neuroprotective potential of the MSC secretome in a rat model of intracerebral hemorrhage and shown that a 10-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Beside exosomes, there is evidence demonstrated that MSC secretome exerted an important role in regulating target cell functions, such as senescence [37], proliferation [20], and migration [38]. Recent studies also confirmed the protective effects of MSC secretome in neural function [39,40]. In this study, we showed that miR-132-3p could improve the effects of MSC EX in protecting neuron function.…”
Section: Discussionsupporting
confidence: 55%
“…Beside exosomes, there is evidence demonstrated that MSC secretome exerted an important role in regulating target cell functions, such as senescence [37], proliferation [20], and migration [38]. Recent studies also confirmed the protective effects of MSC secretome in neural function [39,40]. In this study, we showed that miR-132-3p could improve the effects of MSC EX in protecting neuron function.…”
Section: Discussionsupporting
confidence: 55%
“…Many secreted trophic molecules as components of their secretome from MSCs transplanted by orthotopic and caudal vein injection facilitated the endogenous reparatory mechanism, which ultimately improved the recovery of neurological function after stroke ( Smith and Gavins, 2012 ; Shichinohe et al, 2015 ; Karagyaur et al, 2021 ). MSC transplantation is promising for promoting angiogenesis.…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%
“…Previously, this mechanism of brain tissue recovery (restricted microglial activation) had been assumed [ 20 ] but had not been confirmed experimentally. In contrast, hyperactivation of microglia increases inflammation, expands injury area and aggravates the outcome [ 21 ].…”
Section: Discussionmentioning
confidence: 99%